Analysis Macrozoobenthos Diversity in Way Kalam Waterfall Tourism Lampung Selatan Regency - Septiarila, Fatika (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2021)
This study aims to determine the diversity index of macrozoobenthos and determine the physico-chemical parameters that exist in Way Kalam Waterfall Tourism, South Lampung. This type of research is descriptive quantitative, sampling was carried out at three research stations including macrozoobenthos samples and measurements of physical and chemical parameters of the waters (temperature, brightness, pH, DO, COD, and BOD) using purposive random sampling technique. Sampling macrozoobenthos on the bottom of the water using a shovel. The results showed that the obtained macrozoobenthos consisted of 3 phyla, 4 classes, 6 orders, 9 families, and 63 individuals. The macrozoobenthos diversity index value obtained was in the moderate category. The diversity index value is in the stable community category, and the dominance index is in the low category. The results of the measurement of physical parameters and chemical parameters showed that the waters of the Way Kalam Waterfall tour were not polluted.